Structure, Morphology, Optical, Magnetic and Dielectric Properties of Ni1-xCdxFe2O4 Material Synthesized by Autocombustion Method - Libra, Poppi Darmila; Syukri, Syukri; Stiadi, Yeni; Rahmayeni (Jurnal Riset Kimia, 2025)
Materials with nanoscale dimensions have recently attracted attention due to their outstanding electrical, magnetic, and dielectric capabilities. Electromagnetic materials, known as spinel ferrite MFe2O4 (M = divalent ion), are essential in advanced technology. Cadmium-substituted ferrite spinel with composition Ni1-xCdxFe2O4 (x = 0, 0.1, 0.15, and 0.2) was synthesized by the autocombustion method using citric acid as a fuel agent. X-Ray Diffraction (XRD) confirms that the spinel structure is present in the prepared nanocrystalline ferrites. Fourier Transformed Infrared Spectroscopy (FTIR) spectra showed intensive absorption bands in the 400-600 cm-¹ range corresponding to tetrahedral and octahedral sites. The absorption spectrum of FTIR shifts towards lower wave numbers as the Cd2+ ion concentration increases. Cd2+ ions doping is important for crystal growth, as evidenced by Scanning Electron Microscopy (SEM) images. The band gap energy values of Ni1-xCdxFe2O4 samples are 1.53 eV, 1.46 eV, 1 43eV, 1.42 eV for x=0-0.2, which indicates the samples absorb in visible light. Analysis of magnetic properties with Vibrating Sample Magnetometer (VSM) shows a small hysteresis loop, so Ni1-xCdxFe2O4 is a soft magnetic material. The dielectric constant increases as the Cd2+ ion concentration increases. The characterization outcomes recommend that the compounds can be used for several applications such as memory, and energy storage devices.